Narrative Literature Review: Management of Varicella in Children - Nadila Nanda Azzahra Ruray; Lisa Yuniati; Nadirah Rasyid Ridha (Jurnal EduHealth, 2026)
Chickenpox (varicella) is a common infectious disease in children caused by the Varicella Zoster Virus (VZV). The disease is generally mild and resolves within 5–7 days, with a characteristic rash that rapidly develops into vesicles. However, varicella carries a risk of complications, particularly in infants, immunocompromised children, and young adults. Management of varicella includes symptomatic therapy, antiviral therapy in selected cases, and preventative measures through vaccination and family education. This review aims to summarize strategies for managing varicella in children based on various scientific literature. This study used a narrative literature review method with a reference search strategy from various sources, such as Google Scholar, PubMed, theses, textbooks, and national and international journals relevant to the research topic. The literature used was published between 2020 and 2025. Inclusion criteria included articles discussing the management of varicella in children, while exclusion criteria included articles that were not fully accessible, irrelevant to the research topic, or published outside the specified year range. The data obtained were analyzed descriptively to provide a comprehensive overview of the management approach for varicella in children. The literature review indicates that varicella in children is generally mild, with the main symptoms being a vesicular rash and fever. However, this disease still carries a risk of complications, especially in neonates and children with impaired immune systems. Management in immunocompetent children focuses more on supportive therapy, while antiviral therapy is recommended for high-risk groups. Furthermore, family education, prevention of transmission, and vaccination play a crucial role in reducing the number of complications and the spread of the disease. A holistic and interdisciplinary approach, involving patients, families, and healthcare professionals, has proven effective in accelerating the recovery process, reducing complications, and reducing the overall burden of disease. In conclusion, the management of varicella in children requires a comprehensive strategy through the integration of medical therapy, preventive measures, and family education to improve clinical outcomes and children's quality of life sustainably.